Adaptation and Validation of a Droplet Digital PCR Assay for the Detection of Cryptosporidium spp. and Giardia duodenalis in Buffalo Milk - Andrea Mancusi; Yolande Thérèse Rose Proroga; Orlandina Di Maro; Irene Dini; Carlo Grassi; Esterina De Carlo; Orlando Paciello; Gabriele Di Vuolo; Antonio Bosco; Laura Rinaldi; Giovanna Cappelli (Food Control, 2026)

When green turns costly: The fiscal fallout of EU waste management funds in Italian municipalities - Anna Laura Baraldi; Claudia Cantabene; Alessandro De Iudicibus; Giovanni Fosco; Iacopo Grassi (Ecological Economics, 2026)

Exploring the fatigue phenomenon in individuals with Parkinson’s disease: an Italian multicenter cross-sectional study - Elisabetta Sarasso; Elisa Pelosin; Ilaria Ruotolo; Manuela Maieron; Alessandro Ferrero; Francesca Quarone; Andrea Grassi; Martina Putzolu; Andrea Gardoni; Giovanna Lagravinese; Francesca Di Biasio; Federica Agosta; et al. (Acta Neurologica Belgica, 2026)
Background Fatigue is a common and disabling non-motor symptom in Parkinson’s disease (PD), significantly affecting patients’ quality of life. However, it is often underdiagnosed due to its subjective nature and the lack of a clear definition, hindering the development of effective treatments. Objectives This study aims to investigate the prevalence of fatigue and its associations with sociodemographic factors, disease severity, levodopa equivalent daily dosage (LEDD) and motor, non-motor, and cognitive symptoms in an Italian cohort of patients with PD. Methods An observational cross-sectional study was carried out in three Italian centers from January to May 2024. One hundred PD patients (H&Y ≤ 4) were assessed using validated tools: Parkinson Fatigue Scale (PFS), Fatigue Severity Scale, and Modified Fatigue Impact Scale. Motor and non-motor signs and symptoms, cognitive status, and LEDD were analyzed using non-parametric tests and Spearman’s correlations. Fatigue prevalence was determined based on PFS score ≥ 3.09. Results Fatigue was present in 36% of patients, more prevalent in women and more severe in those with H&Y > 2. Fatigue correlated strongly with non-motor symptoms (MDS-UPDRS Part I; ρ > 0.6, p p p Conclusions Fatigue in PD is a multidimensional phenomenon influenced mainly by non-motor symptoms. Gender-specific differences and the association with disease progression underscore the need of comprehensive and integrated management strategies to address this challenging symptom.

Valorisation of freshwater weeds biomass to produce bio-based composites through do-it-yourself approach - Laura Dominici; Anna Fornaseri; Martina Grassi; Dumitru Moraru; Marco Sangermano; Raffaella Sesana; Elena Comino (Journal of Cleaner Production, 2025)

Into the backyard: Multiple detections of PCV-2e in rural pig farms of Northern Italy. An unexpected ecological niche? - Giulia Faustini; Claudia Maria Tucciarone; Matteo Legnardi; Laura Grassi; Giacomo Berto; Michele Drigo; Mattia Cecchinato; Giovanni Franzo (Preventive Veterinary Medicine, 2023)

Investigation of Carnivore protoparvovirus 1 and Amdoparvovirus infections in red fox populations of the Italian Dolomites - Laura Grassi; Maria Luisa Menandro; Federica Obber; Michele Drigo; Matteo Legnardi; Daniela Pasotto; Claudia Maria Tucciarone; Giulia Faustini; Carlo Citterio; Mattia Cecchinato; Giovanni Franzo (Veterinary Research Communications, 2022)

Clinical impact of rare variants associated with inherited channelopathies: a 5-year update - Georgia Sarquella-Brugada; Anna Fernandez-Falgueras; Sergi Cesar; Elena Arbelo; Mónica Coll; Alexandra Perez-Serra; Marta Puigmulé; Anna Iglesias; Mireia Alcalde; Marta Vallverdú-Prats; Victoria Fiol; Carles Ferrer-Costa; et al. (Human Genetics, 2022)
A proper interpretation of the pathogenicity of rare variants is crucial before clinical translation. Ongoing addition of new data may modify previous variant classifications; however, how often a reanalysis is necessary remains undefined. We aimed to extensively reanalyze rare variants associated with inherited channelopathies originally classified 5 years ago and its clinical impact. In 2016, rare variants identified through genetic analysis were classified following the American College of Medical Genetics and Genomics’ recommendations. Five years later, we have reclassified the same variants following the same recommendations but including new available data. Potential clinical implications were discussed. Our cohort included 49 cases of inherited channelopathies diagnosed in 2016. Update show that 18.36% of the variants changed classification mainly due to improved global frequency data. Reclassifications mostly occurred in minority genes associated with channelopathies. Similar percentage of variants remain as deleterious nowadays, located in main known genes ( SCN5A, KCNH2 and KCNQ1 ). In 2016, 69.38% of variants were classified as unknown significance, but now, 53.06% of variants are classified as such, remaining the most common group. No management was modified after translation of genetic data into clinics. After 5 years, nearly 20% of rare variants associated with inherited channelopathies were reclassified. This supports performing periodic reanalyses of no more than 5 years since last classification. Use of newly available data is necessary, especially concerning global frequencies and family segregation. Personalized clinical translation of rare variants can be crucial to management if a significant change in classification is identified.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Neuronal membrane dynamics as fine regulator of sphingolipid composition - Massimo Aureli; Maura Samarani; Nicoletta Loberto; Elena Chiricozzi; Laura Mauri; Sara Grassi; Domitilla Schiumarini; Alessandro Prinetti; Sandro Sonnino (Glycoconjugate Journal, 2018)

Not the one, but the only one: about Cannabis cryptic virus in plants showing ‘hemp streak’ disease symptoms - Laura Righetti; Roberta Paris; Claudio Ratti; Matteo Calassanzio; Chiara Onofri; Davide Calzolari; Wulf Menzel; Dennis Knierim; Gianmaria Magagnini; Daniela Pacifico; Gianpaolo Grassi (European Journal of Plant Pathology, 2018)

Placental aging and oxidation damage in a tissue micro-array model: an immunohistochemistry study - Ambrogio P. Londero; Maria Orsaria; Stefania Marzinotto; Tiziana Grassi; Arrigo Fruscalzo; Angelo Calcagno; Serena Bertozzi; Nastassia Nardini; Enrica Stella; Ralph J. Lellé; Lorenza Driul; Gianluca Tell; et al. (Histochemistry and Cell Biology, 2016)

Lipid Rafts in Neurodegeneration and Neuroprotection - Sandro Sonnino; Massimo Aureli; Sara Grassi; Laura Mauri; Simona Prioni; Alessandro Prinetti (Molecular Neurobiology, 2014)

Placental hCG immunohistochemistry and serum free-Beta-hCG at 11–13 weeks’ gestation in intrauterine fetal demise - Ambrogio P. Londero; Maria Orsaria; Tiziana Grassi; Angelo Calcagno; Stefania Marzinotto; Maria Ceraudo; Arrigo Fruscalzo; Lorenza Driul; Laura Mariuzzi (Histochemistry and Cell Biology, 2013)

Inhibitory effects of fenofibrate on apoptosis and cell proliferation in human endothelial cells in high glucose - Michela Zanetti; Alessia Stocca; Barbara Dapas; Rossella Farra; Laura Uxa; Alessandra Bosutti; Rocco Barazzoni; Fleur Bossi; Carlo Giansante; Francesco Tedesco; Luigi Cattin; Gianfranco Guarnieri; et al. (Journal of Molecular Medicine, 2008)